2006
DOI: 10.1093/pasj/58.2.313
|View full text |Cite
|
Sign up to set email alerts
|

Lyα Emitters at z = 5.7 in the Subaru Deep Field

Abstract: We present the properties of Lyα emitters (LAEs) at z = 5.7 in the Subaru Deep Field. A photometric sample of 89 LAE candidates is constructed from narrow-band (NB816) data down to N B816 = 26.0 (AB) in a continuous 725 arcmin 2 area. Spectra of 39 objects satisfying the photometric selection criteria for LAEs were obtained with Subaru and Keck II Telescopes, among which 28 were confirmed LAEs, one was a nearby galaxy, and eight were unclassified. We also obtained spectra of another 24 NB816-excess objects in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
420
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 291 publications
(476 citation statements)
references
References 62 publications
(79 reference statements)
49
420
7
Order By: Relevance
“…At higher redshift (z 4), emitters with EWs larger than 240 Å have been predicted (Schaerer 2003;Tumlison et al 2003) and observed (Malhotra & Rhoads 2002;Shimasaku et al 2006;Stanway et al 2007). These large EWs supposedly cannot be explained by a normal initial mass function but have been proposed to be signs of Population III stars.…”
Section: Equivalent Width Distributionmentioning
confidence: 85%
See 1 more Smart Citation
“…At higher redshift (z 4), emitters with EWs larger than 240 Å have been predicted (Schaerer 2003;Tumlison et al 2003) and observed (Malhotra & Rhoads 2002;Shimasaku et al 2006;Stanway et al 2007). These large EWs supposedly cannot be explained by a normal initial mass function but have been proposed to be signs of Population III stars.…”
Section: Equivalent Width Distributionmentioning
confidence: 85%
“…Objects with large equivalent widths (EWs) are thus selected by comparing the colours in the narrow-band image and complementary broad-band images. Spectroscopically confirmed Lyα emitters now include several hundreds of sources at redshifts z ∼ 3 (e.g., Møller & Warren 1993;Cowie & Hu 1998;Steidel et al 2000;Fynbo et al 2001Fynbo et al , 2003aMatsuda et al 2005;Venemans et al 2007;Nilsson et al 2007;Ouchi et al 2008), z ∼ 4.5 (Finkelstein et al 2007), z ∼ 5.7 (Malhotra et al 2005;Shimasaku et al 2006;Tapken et al 2006) and z ∼ 6.5 (Taniguchi et al 2005;Kashikawa et al 2006). However, in the low redshift range, between z ≈ 1.6 corresponding to the atmospheric cut-off in the UV and z ∼ 3, little progress has been made.…”
Section: Introductionmentioning
confidence: 99%
“…An independent test of the determined AGN fraction is to calculate the LAE volume density by dividing a known AGN volume density by the LAE AGN fraction. For this test, we used the AGN comoving volume densities as determined observationally by Bongiorno et al (2007) and theoretically by Hopkins et al (2007), and we compared them with comoving LAE volume densities from eighteen different publications (Steidel et al 2000;Stiavelli et al 2001;Dawson et al 2004;Hayashino et al 2004;Shimasaku et al 2006;Nilsson et al 2007;Gronwall et al 2007;Venemans et al 2007;Murayama et al 2007;Prescott et al 2008;Deharveng et al 2008;Ouchi et al 2008;Grove et al 2009;Shioya et al 2009;Guaita et al 2010;Bongiovanni et al 2010;Yuma et al 2010). In Fig.…”
Section: Agn and Lae Volume Density Evolutionmentioning
confidence: 99%
“…More interestingly, it has been theoretically predicted that galaxies hosting zero-metallicity stars (or Population III stars, hereafter PopIII) should show huge Lyα equivalent widths that could reach up to EW 0 ∼ 1000 Å (e.g., Schaerer 2002Schaerer , 2003Tumlinson et al 2003;Scannapieco et al 2003). Therefore, the frequency distribution of the Lyα equivalent width in high-z galaxies and its evolution with redshift are important for understanding the early stages of galaxy evolution (e.g., Shimasaku et al 2006;Ando et al 2006). …”
Section: Introductionmentioning
confidence: 99%